A metastable rRNA junction essential for bacterial 30S biogenesis - Sharma, Indra Mani (Nucleic Acids Res, 2018)
Tertiary sequence motifs encode interactions between RNA helices that create the three-dimensional structures of ribosomal subunits. A Right Angle motif at the junction between 16S helices 5 and 6 (J5/6) is universally conserved amongst small subunit rRNAs and forms a stable right angle in minimal RNAs. J5/6 does not form a right angle in the mature ribosome, suggesting that this motif encodes a metastable structure needed for ribosome biogenesis. In this study, J5/6 mutations block 30S ribosome assembly and 16S maturation in Escherichia coli. Folding assays and in-cell X-ray footprinting showed that J5/6 mutations favor an assembly intermediate of the 16S 5′ domain and prevent formation of the central pseudoknot. Quantitative mass spectrometry revealed that mutant pre-30S ribosomes lack protein uS12 and are depleted in proteins uS5 and uS2. Together, these results show that impaired folding of the J5/6 right angle prevents the establishment of inter-domain interactions, resulting in global collapse of the 30S structure observed in electron micrographs of mutant pre-30S ribosomes. We propose that the J5/6 motif is part of a spine of RNA helices that switch conformation at distinct stages of assembly, linking peripheral domains with the 30S active site to ensure the integrity of 30S biogenesis.